EXPLORING THE FACTORS THAT INFLUENCE INDONESIAN AUDITORS' INTENTION TO USE BIG DATA ANALYTICS: APPLICATION OF THE UTAUT MODEL WITH PERCEIVED RISK AND TRUST - Levi, Chrisrian; Angelus, Michael (Journal of Applied Finance and Accounting, 2024)
The adoption of Big Data Analytics (BDA) in auditing is vital in the fourth industrial revolution era, yet imany auditors in Indonesia hesitate to embrace these tools. This study aims to identify factors influencing Indonesian auditors' intention to use BDA, applying the Unified Theory of Acceptance and Use of Technology (UTAUT) model and including perceived risk and trust variables. Using quantitative approach, questionnaires were distributed via Google Form to 134 auditor respondents in Indonesia, primarily in DKI Jakarta. Data were analyzed using Structural Equation Modeling (SEM) with SmartPLS. Result shows that performance expectancy, effort expectancy, social influence, and trust significantly influence auditors' intention to use BDA, while perceived risk does not significantly affect the intention to use BDA. This study underscores the importance of strengthening auditor trust in technology to enhance BDA adoption, with training and technical support identified as supportive factors to increase auditor comfort and confidence in using BDA in the future, also future research could explore the longitudinal impacts of BDA adoption or extend the study to diverse industries and regions.